SEMANTIC ANALYSIS OF ḤANĪF: AN AFFIRMATION OF THE ONENESS OF GOD - Zubaidi Saleh, Sujiat; Qorib, Khoffifa Assakhyyu; Dwi Syafitri, Aprilia (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
This article is based on the human paradigm which recognizes that the Prophet Ibrahim was the father of three samawī religions. This paradigm influences the ideology of religious communities. The researcher semantically interprets the ḥanîf sentence by examining the meaning of hanīf based on its history. The study concludes that ḥanîf means someone who turns away from evil, leans towards goodness and truth, always turns himself towards the Qibla of Baitul Haram, sincere in his worship, accepting all commands of Allah, and steadfast in the way of Allah, obeying all commandments without the slightest deviation. The meaning of ḥanîf therefore proves the monotheism of Prophet Ibrahim AS and his complete adherence to the religion of Allah.